Far-Infrared Fourier Transform Spectroscopy of NTD Ge and GeᵪSi₍₁_ᵪ₎/Si Heterostructures - Jang, Fan Ho (My University, 1989)
Far-infrared Fourier transform spectroscopy is used to investigate the excited states of impurities in semiconductors. Two different research projects are presented. The first involves an investigation of the far-infrared absorption of compensated p-type Ge at a temperature of 3 K. The abosorption mechanism which is of interest is due to photon-induced hopping transitions of charge carriers between impurity centers. The samples were prepared by neutron transmutation doping (NTD). It is found that the absorption spectra for samples with carrier concentrations (Na - Nd) ranging from 2.3x10¹⁵ to 2.6x10¹⁶ cmˉ³ show a broad absorption with the maximum occuring at a frequency between 10 and 24 cmˉ¹. The absorption coefficient of this maximum ranges between 2 and 87 cmˉ¹. The dynamical change of absorption due to the evolution of the Ga impurity is also presented. The absorption and the frequency of its maximum increase asymptotically with respect to time. It is found that at low frequencies, the absorption coefficient is proportional to frequency. The overall behavior of the absorption spectra is found to be consistent with a theory based on the localized pair model. E. Kaczmarek and Z. W. Gortel have theoretically predicted a sharp peak at 20.4 cmˉ¹ on the absorption curve. Its position is independent of the compensation or the impurity concentration of the sample. However, this peak has not been observed in the experimental absorption spectra.
The second project involves the investigation of shallow impurities in selectively boron-doped GeᵪSi₍₁_ᵪ₎/Si strained-layer heterostructures using far-infrared photothermal ionization spectroscopy (PTIS). The spectra are obtained under various experimental conditions: with and without band-edge light and by varying the temperature of, and voltage applied to, the sample. The transport properties: resistivity, sheet charge density and Hall hole mobility of these samples are presented. It is found that a sample with a two-dimensional hole gas (2-DHG) behavior at the GeᵪSi₍₁_ᵪ₎/Si interface has a weak photoresponse. This is due to the small number of photogenerated carriers in comparison with the residual hole carriers. For samples which do not show 2-DHG behavior, the photoresponse from the substrate plays the dominant role for low applied voltages. At higher voltages, the response from the epitaxial layers becomes evident. The majority impurity was identified as the intentional dopant boron and the dominant minority impurity was found to be phosphorus. It is concluded that although the free carriers are generated in the heavily B-doped layer, those carriers conducted through the low energy, high mobility GeᵪSi₍₁_ᵪ₎/Si interface layer, will dominate the photoresponse.
Keywords: Physics